2012
DOI: 10.1073/pnas.1107736109
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of multiple misfolding pathways in a single prion protein molecule

Abstract: Protein misfolding is a ubiquitous phenomenon associated with a wide range of diseases. Single-molecule approaches offer a powerful tool for deciphering the mechanisms of misfolding by measuring the conformational fluctuations of a protein with high sensitivity. We applied single-molecule force spectroscopy to observe directly the misfolding of the prion protein PrP, a protein notable for having an infectious misfolded state that is able to propagate by recruiting natively folded PrP. By measuring folding traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
194
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 140 publications
(203 citation statements)
references
References 55 publications
7
194
0
2
Order By: Relevance
“…Landscape reconstructions based on high-bandwidth equilibrium measurements of the extension at constant force or trap separation typically provide higher spatial resolution (20,22). However, equilibrium trajectories present interpretation difficulties for PrP, because in addition to native folding they also contain transitions into shortlived, nonnative states accessible only from the unfolded state (28,30), which would distort the reconstructed landscape. In contrast, unfolding FECs always go first from N to U, with subsequent refolding into the misfolded states suppressed by virtue of the nonequilibrium conditions caused by the fast force-ramp rate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Landscape reconstructions based on high-bandwidth equilibrium measurements of the extension at constant force or trap separation typically provide higher spatial resolution (20,22). However, equilibrium trajectories present interpretation difficulties for PrP, because in addition to native folding they also contain transitions into shortlived, nonnative states accessible only from the unfolded state (28,30), which would distort the reconstructed landscape. In contrast, unfolding FECs always go first from N to U, with subsequent refolding into the misfolded states suppressed by virtue of the nonequilibrium conditions caused by the fast force-ramp rate.…”
Section: Resultsmentioning
confidence: 99%
“…As an independent test of whether this overall picture is correct, we analyzed equilibrium measurements of the extension at constant force, in the range approximately 8-10 pN. Previous work has shown that the native folding pathway did not include any intermediate state (28,30). Representative records at different forces (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations